The Histological Effect of Aeromonashydrophila on liver of male albino mice (Baghdad Science Journal, 2013)
Two hundred of stool samples from different age groups(less than 5 to 40 years) were collected from Al-Elwea , Al-Kendy , Children welfare and Baghdad Teaching hospital from September 2009 to May 2010 . Using the isolation methods & diagnostic laboratory tests, Aeromonashydrophila was isolated according to the growth on MacConkey , blood &TCBS agar . The sensitivity test for diagnostic antibiotic O129 was done , also by biochemical test using api20E . The percentage of isolation for Aeromonashydrophila was 5% for all patients . The hemolysin assay was also done to select the proper isolate for the study . The isolate 2 showed high activity for hemolysin at its 640 unit/ ml by using human blood . The LD50 was detected and found it was 1010 bacterium / mouse when orally administrated in this study using 28 male of albino mice age 6-8 weeks and weight 20-25 g were divided into 4 group (7 mice / groups and were orally administrated with 0.2 ml of inoculums 104 , 106 , 108 bacterium / mouse) for 10 days . These results show pathological changes in liver after 10 days . The changes include congestion ,hemorrhage , degeneration & necrosis . Tha bacteria Aeromonashydrophila had a wide spread & can infect all age groups & it had a negative effect on liver